Burnout syndrome in Spanish university lecturers: prevalence and relationship with lifestyle habits and physical and mental health indicators - Colado-Tello, María Estela; Jiménez-Boraita, Raúl; Gargallo-Ibort, Esther; Dalmau-Torres, Josep María (BMC Psychology, 2026)
Background Teaching requires intense engagement. Adaptive changes and work demands have an effect on the health of university lecturers, which carries a risk of burnout. The present study aimed to determine the prevalence of burnout syndrome among Spanish university lecturers and to analyse its relationship with lifestyle habits and physical and mental health indicators. Methods The study was carried out on a sample of 1560 university lecturers (47.39 ± 11.29 years) from thirteen universities belonging to the Spanish Network of Health Promoting Universities. Burnout, health-related quality of life, stress, anxiety and depression, vocal fatigue, physical activity, sedentary habits, eating behaviour and sleep quality were all assessed. Results Among Spanish university lecturers, emotional exhaustion rates of 20.83% were reported, alongside depersonalisation rates of 5.26% and low self-fulfilment rates of 49.74%. Regression analysis revealed that emotional exhaustion is negatively associated with physical, mental and environmental wellbeing, as well as being positively associated with stress, depression, vocal fatigue and uncontrolled eating. On the other hand, depersonalisation was negatively associated with social relationships and positively associated with stress, depression and vocal fatigue. Finally, the self-fulfilment aspect was positively associated with social relationships, mental wellbeing and voice improvement with rest, whilst also being negatively associated with vocal fatigue. Conclusions Present findings reveal the association of multiple factors with burnout risk among university lecturers. These findings can serve as a basis on which to design interventions aimed at promoting health and wellbeing from within university institutions or policies concerned with university lecturers’ health.
Keywords: health; university teachers; burnout; lifestyle; mental disorders